Applied Macroeconometrics - Aslanidis, Nektarios (Altres títols, 2017)
This book treats econometric methods for analysis of applied econometrics with a particular focus on applications in macroeconomics. Topics include macroeconomic data, panel data models, unobserved heterogeneity, model comparison, endogeneity, dynamic econometric models, vector autoregressions, forecast evaluation, structural identification. The books provides undergraduate students with the necessary knowledge to be able to undertake econometric analysis in modern macroeconomic research.